2015
DOI: 10.1136/bmjopen-2015-008266
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for non-participation in the Northern Ireland Bowel Cancer Screening Programme: a qualitative study

Abstract: ObjectivesTo identify the reasons why some people do not participate in bowel cancer screening so that steps can be taken to improve informed decision-making.DesignQualitative study, using focus groups with thematic analysis of data to identify, analyse and report patterns. Transcripts were repeatedly read and inductively coded using a phenomenological perspective, and organised into key themes.SettingBelfast and Armagh, two areas of Northern Ireland with relatively low uptake of bowel cancer screening.Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Often the cases they discussed emphasised harrowing treatment, pain and death and did not discuss the benefits of early detection, despite being favourable towards the ethos of screening. Non-screeners certainly articulated the 'rather not know' position, a position that has been commonly reported in other studies (Bradley et al, 2015;Honein-AbouHaidar et al, 2016;Lipworth, Davey, Carter, Hooker & Hu, 2010) though some went further by stating that they would know if they had cancer because they were sure that they would experience symptoms, which echoes work done by others (Austin et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…Often the cases they discussed emphasised harrowing treatment, pain and death and did not discuss the benefits of early detection, despite being favourable towards the ethos of screening. Non-screeners certainly articulated the 'rather not know' position, a position that has been commonly reported in other studies (Bradley et al, 2015;Honein-AbouHaidar et al, 2016;Lipworth, Davey, Carter, Hooker & Hu, 2010) though some went further by stating that they would know if they had cancer because they were sure that they would experience symptoms, which echoes work done by others (Austin et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…12 20 28 These concerns were evident across most participants, however, comparisons of accounts between screeners and non-screeners showed that when there is a strong perceived need for reassurance about potential cancer presence, concerns about the invasiveness of the test and other practical barriers were more readily overcome. The concept of ‘perceived need for reassurance’, as described in our analysis, reflects an appraisal response to the activation of emotional reactions triggered by the screening invitation, specifically in relation to beliefs about personal risks and circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors play a part in the reasons for non-participation in screening, including socioeconomic status, ethnicity, age, and gender [ 38 ]. The nature of the test procedure itself has also been reported as a reason for non-participation in CRC screening [ 39 , 40 ]: this is one of the reasons that many gFOBtbased programs are moving to FIT-based screening.…”
Section: How Should We Screen?mentioning
confidence: 99%